Performance Evaluation of a Small Scale Modular Solar Trigeneration System - Handong Wang (International Journal of Photoenergy)
In order to improve the efficiency of solar thermal power (STP) system, a novel modular system combining cooling, heating, and power generation (CCHP) is proposed and introduced in this work. This modular CCHP system can simultaneously provide 10 kW electricity, −15~5°C coolant, and 60°C hot water to meet the requirements of cooling, heating, and electricity in a general family or other fields. The flow chart and working process of the modular system are introduced, based on which the energy and exergy efficiencies at the CCHP and STP operation modes are primarily evaluated and discussed. The results show that when the output electricity is constant, the overall efficiencies of energy and exergy of the system operating at the CCHP mode are 9.37 times and 2.62 times as big as those of the system operating at the STP mode, respectively. Thus, the modular solar thermal CCHP system can improve the energy and exergy efficiencies. Furthermore, calculation shows that both the overall energy and exergy efficiencies decrease with increase of inlet vapor temperature at given inlet vapor pressure, but both the efficiencies increase with increase of inlet vapor pressure at given inlet temperature.